Building Multidisciplinary Research Capacity in Emerging Provincial Universities: Challenges, Collaboration, and Global Lessons for Nepal (OCEM Journal of Management, Technology & Social Sciences, 2026)
Research capacity development is crucial for higher education institutions seeking to address complex societal issues through multidisciplinary approaches. This study focuses on emerging provincial universities in Nepal that face significant structural and institutional constraints hindering research productivity and academic advancement. This study investigated factors affecting multidisciplinary research capacity, highlighting institutional barriers, collaborative practices, and lessons from international settings. A qualitative design was used, following content analysis of semi-structured interview data with four academicians engaged in higher education. Findings show that, despite increased investment, provincial universities are struggling with inadequate research infrastructure, limited funding, a weak research culture, bureaucratic inefficiencies in grant management, and a lack of institutional support. Key determinants identified for research development include institutional governance, organisational capacity, and academic competencies.This study underscores the importance of interdisciplinary and trans-disciplinary research in addressing current social, economic, and environmental challenges, while recognising the limitations of traditional academic structures. National and international collaborations are crucial for enhancing research capacity through knowledge sharing and innovation, though challenges such as unequal partnership dynamics and limited academic writing skills constrain global research visibility.Additionally, this study advocates for community-based and participatory research to boost societal relevance and impact. Insights from Indonesia and the Netherlands reveal that institutional autonomy, policy innovation, and flexible curricula are essential for promoting cross-disciplinary collaboration. Ultimately, strengthening research capacity in Nepal requires integrated strategies that include researcher skill development, supportive institutional policies, equitable collaborative networks, and ensuring association between research goals and societal demands.